Research using free text data in medical records could benefit from dynamic consent and other tools for responsible governance - Morrison, Michael (Journal of medical ethics, 2020)
As the capacity to generate, store, aggregate and combine ever greater volumes and types of data about individuals, behaviours and interactions continues to expand apace, so too does the challenge of ensuring suitable and appropriate governance of that data. In broad terms, the challenge is simple; how to ensure the (public) benefits of data, such as improvements in service delivery or individual and collective well-being, while avoiding harms such as discrimination, injustice or placing undue burdens on individuals and groups. The difficulty, as ever, lies in the details. As Nicol et al 1 observe, informed consent is important but does not replace the need for an appropriate governance framework that covers the wider ecosystem of data generation, use and reuse. Moreover, there is no one universal oversight mechanism for data sharing, but what counts as ‘appropriate’ must take into account the context and purpose of data use. In this regard, the study by Ford et al is an important and valuable contribution to our understanding of the …